A Machine Learning and Blockchain-Based Framework for Enhanced Intrusion Detection Systems Using the CSE-CIC-IDS2018 Dataset - Saidi, Zakariae; Ouidad, Akhrif; El Idrissi Younes, El Bouzekri (Informatica, 2025)
Intrusion Detection Systems (IDS) are critical in shielding digital infrastructures from cyber threats. This paper discusses a hybrid method to enhance a Host-based IDS (HIDS) detection and trustworthiness by incorporating Machine Learning (ML) into Blockchain. We used the CSE-CIC-IDS2018 dataset to benchmark various ML classifiers, including Decision Tree, Random Forest, Support Vector Machine, and XGBoost, all according to standard metrics of accuracy, precision, recall, and F1 score, even with potential class imbalance in the dataset. Between the classifiers examined, the XGBoost algorithm performed the best of all; prior to feature selection, the F1 score averaged 0.98 in a binary classification and 0.80 for the multiclass classification. Following the application of the SelectKBest method the performance played a role dropped to 0.73 (binary) and 0.55 (multiclass), indicating that model accuracy is sensitive to reducing feature selection methods.We proposed a blockchain-enabled log management and integrity monitoring system for an HIDS, which used a private Proof of Authority (PoA) Blockchain and smart contracts for evidence collection. The proposed system is intended to allow tamper-resistant logs, as well as automated event alerts if the logs had been tampered with. We conducted preliminary and simulated tests and showed that the system detected a lack of integrity and evidence with low resource overhead. This study contributes to the design of resilient, intelligent IDS architectures and outlines future directions for integrating adaptive detection with secure, decentralized log management.